Non-linear dynamics in bilateral Malaysian Ringgit - U.S. Dollar spot rates - Lim, Kian Ping; Azali, M.; Habibullah, Muzafar Shah (Universiti Utara Malaysia, 2003)
This study empirically investigates the presence of non-linearity in the Malaysian exchange rates returns series. Our bispectrum results reveal that the underlying generating process of the Malaysian exchange rates is governed by non-linear dynamics. With this evidence of non-linearity, researchers can no longer take the linear assumption for granted as it has profound implications on the robustness of their empirical results. Thus, this study points to the need to employ formal linearity test as a preliminary diagnostic tool to determine the nature of the data generating process of the series under investigation before any further empirical analysis.